2017
DOI: 10.1161/circheartfailure.117.004417
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-Specific Bdh1 Overexpression Ameliorates Oxidative Stress and Cardiac Remodeling in Pressure Overload–Induced Heart Failure

Abstract: We demonstrated that ketone body oxidation increased in failing hearts, and increased ketone body utilization decreased oxidative stress and protected against heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 29 publications
5
79
1
1
Order By: Relevance
“…3, G-I, and 4). Thus, the present model of MI-induced HF did not have upregulated ketone oxidation in the myocardium in contrast to HF models in earlier studies (Schugar et al, 2014;Aubert et al, 2016;Bedi et al, 2016;Diakos et al, 2016;Uchihashi et al, 2017), possibly because the duration of cardiac overload (12 hours vs. 4-8 weeks), severity of HF (post-MI vs. aortic banding model), and/or presence of DM were different. Nevertheless, treatment with empagliflozin increased blood and myocardial bOHB levels by approximately 2-and 10-fold, respectively, and the increased tissue level of bOHB was accompanied by preservation of ATP level after MI.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…3, G-I, and 4). Thus, the present model of MI-induced HF did not have upregulated ketone oxidation in the myocardium in contrast to HF models in earlier studies (Schugar et al, 2014;Aubert et al, 2016;Bedi et al, 2016;Diakos et al, 2016;Uchihashi et al, 2017), possibly because the duration of cardiac overload (12 hours vs. 4-8 weeks), severity of HF (post-MI vs. aortic banding model), and/or presence of DM were different. Nevertheless, treatment with empagliflozin increased blood and myocardial bOHB levels by approximately 2-and 10-fold, respectively, and the increased tissue level of bOHB was accompanied by preservation of ATP level after MI.…”
Section: Discussioncontrasting
confidence: 82%
“…On the other hand, ketone oxidation increases to compensate for the decrease in acetyl CoA production in the failing heart (Aubert et al, 2016;Bedi et al, 2016). Recently, it has been reported that cardiac-specific overexpression of BDH1 was protective in mice, while knockout of SCOT was detrimental to HF induced by pressure overload (Schugar et al, 2014;Uchihashi et al, 2017). These results support the notion that promotion of ketone oxidation improves the energy metabolism in failing hearts.…”
Section: Discussionsupporting
confidence: 57%
“…Regardless, the results of the Oxct1 -/and csBDH1 -/mice, together with the observed increase in 3OHB oxidation in the failing heart that occurs in the context of reduced utilization of fatty acids, suggest that ketone bodies are being used as an alternate oxidative fuel in order to maintain adequate ATP generation. This result is further supported by the recent observation that transgenic mice overexpressing BDH1 exhibit less pathologic remodeling in response to TAC (42).…”
Section: Discussionsupporting
confidence: 69%
“…d-β-hydroxybutyrate dehydrogenase I (BDH1) promotes the interconversion of acetoacetate and β-hydroxybutyrate. Cardiac-specific overexpression of BDH1 promotes the expression of antioxidants to diminish ROS levels and reverse oxidative stress-induced DNA injury to attenuate heart failure [139]. Collectively, the physiological level of ketone bodies such as β-hydroxybutyrate protects cells from oxidative stress and prevents the acceleration of cardiac remodeling.…”
Section: Butyrate and Butyrylationmentioning
confidence: 99%